(3GdLhGfH GdbGfhfjI ddJYGed aj CSge GdNRjfI (B: s (3OQGSI ebGQfI (B/ s - (3YHOGddg YeQ eMehO GdPfjHGJ s; (3CMeO aGQhb hTGMj s; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2017)
(3gOaJ GdOQGSI Gdi JMOjO GdebUhO HCSge GdNRjfI Ydi CfgG YbO HjY JMUd HebJVGg GdTQcI Ydi GdCSge GdeHGYI HSYQgG aj Shb GdChQGb GdeGdjI(B: (3ShGA bGeJ Hg GdTQcI HfaSgG Ch HhGSWI TNU jJUQa HCSeg hdMSGHI(B: (3hHeLQO EJeGe GdHjY dG jchf ddHGFY(B( (3GdeSGge(B) (3GdMb aj GdMUhd Ydi CSge JeJY(B: (3hPdc dEfbWGY UdJg cdjkG HeLQO GdHjY HGdTQcI(B. (3hbSeJ GdOQGSI (B((3daUd JegjOj(B) (3NUU dOQGSI eGgjI TQGA GdTQcI dCSge GdNRjfI(B: (3hHGHjf QFjSjjf (B: (3NUU GdChd efgeG ddCSGS GdbGfhfj ddJYGed HCSge GdNRjfI(B: (3hCeG KGfjgeG aNUU ddbjhO GdELQGFjI Ydi YedjI TQGA CSge GdNRjfI(B. (3hJhUdJ GdOQGSI Gdi eLehYI ef GdfJGFL ef CgegG(B: (3Cf GdabI cGf jJWQb Edi YedjI TQGA CSge GdNRjfI bHd Cf jJe JfXjegG JTQjYjkG HEYJHGQgG WQjbI NGUI ef WQb JNajV Ch ESJgdGc QCS GdeGd(B. (3Edi Cf Je MUQ GdMGdGJ GdJj jecf ddTQcI GdbjGe HTQGA CSge GdNRjfI hPdc HYO hVY GdEWGQ GdbGfhfj dYedjI TQGA CSge GdNRjfI hJMOjOgG Ydi SHjd GdMUQ (B((3JNajV QCS GdeGd(B: (3dJhRjYgG Ydi GdYGedjf aj GdTQcI(B: (3GdTQGA GdeQJHW HTQW GdehGabI(B). (3MjK dG JfWhj gPg GdMGdGJ GdESJKfGFjI Ydi CjI NWhQI ShGA ef MjK GdENdGd HGdeUGdM GdeJOGNdI aj GdYedjI Ch ef MjK GdSeGM ddTQcI HGdeVGQHI Ydi CSgegG aj Shb GdChQGb GdeGdjI(B. s
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdYGe, (B2017 s
(3HHdjhLQGajG(B: (3UaMGJ (B272-283s
Keywords: (3GdbGfhf GdYGes; (3CSge GdNRjfIs; (3GdLhGfH GdbGfhfjI s; (3TQGA CSge GdNRjfIs; (3GdbjhO GdGLQGFjI Ydi YedjI TQGA GSge GdNRjfIs; (3GdGMcGe GdeJQJHI Ydi TQGA GSge GdNRjfIs; (3GdGSGS GdbGfhfj ddJYGed HGSge GdNRjfIs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdYGes